Estimation of requirements for signal parameters at V-shaped frequency distribution in the mathematical model of a planar phased array antenna - Kovalenko, A.I.; Titov, S.V.; Titova, E.V.; Chorna, O.S. (Radiotekhnika, 2023)
A brief review provides methods of focusing electromagnetic radiation of a flat phased array antenna based on mutually consistent spatial-amplitude-phase-frequency control of the radiated signals and limitations of their potential capabilities arising from various random fluctuations of signal and antenna parameters. The performed statistical study revealed the influence of various random and deterministic changes in the electrical and structural parameters of antennas, control systems for radiated signals with a V-shaped frequency distribution over the aperture of a flat phased array on the peak power level, duration, and repetition period of focused pulses. The parameters of the law of spatial-amplitude-phase-frequency control should be stable for a time equal to the average pulse duration at the output of the emitters when forming a single spatiotemporal pulse, and when forming a sequence of spatiotemporal pulses within duration of this packet of spatiotemporal pulses. The requirements for the accuracy and stability of parameters of the space-phase-frequency signal control law are considered. The analyses of influence of various deviations from the set values of the parameters of the law of spatial-phase-frequency control of emitted signals in the channels of a multi-position system of emitters in the formation of sequences of spatiotemporal pulses is analyzed. It is shown that the influence of errors in the location of the phase centers of the emitters in the direction of radiation does not depend on the distance to the focusing point, but is significant and requires special measures to reduce them. The influence of initial phase setting errors on the characteristics of the generated sequence of spatiotemporal pulses also does not depend on the radiation time. The range of permissible values of the maximum initial phase setting errors behind the aperture of a flat phased antenna array, in which the decrease in the power flux density value does not exceed 10%, should not exceed p/3. The discreteness and random errors in establishing the initial phases of individual radiation sources of a flat phased array equal to p/3 practically do not affect the duration and repetition period of the sequence of spatiotemporal pulses.